Twin Deficits Phenomenon: Causality in Frequency Domain Approach - Gurkanyay, Gulsun; Tastan, Huseyin (ISTANBUL UNIV, 2007)
This paper examines the twin defic its hypothesis for U.S.A., Argentina, Brazil, Mexico, Korea, the Philippines, Thailand and Turkey. In addition to Granger-causality tests in the time domain, this study employs causality tests in the frequency domain and spectral variance decomposition. The results from causality tests in the frequency domain can be summarized as follows : (i) there exists a significant causal relationship from budget deficits to current account defic its in the long run for Thailand and Brazil. (ii) The same causality relationship is found to be ins ignificant at all frequencies for Mexico, the Philippines and Turkey. (iii) The relationship is significant at high frequencies (short run) for Korea, Argentina and U.S.A. (iv) The causality from current account defic its to fiscal defic its is found to be significant in the long run for Argentina and Turkey. Albeit weak, similar causality relationship is found for U.S.A. (v) And finally, for Korea, Mexico, the Philippines, Brazil and Thailand, the causality from foreign deficits to budget deficits is found to be significant only in the short run (at high frequencies).
Keywords: Twin Deficits Hypothesis; Granger-causality in the Frequency Domain; Spectral Analysis; Government & Law